Investigation the Optimization of Machining Parameters to Surface Roughness in Free Form Surface of Composite Material - Kazaal, Reem S.; Hamdan, Wisam K. (Al-Khwarizmi Engineering Journal, 2019)
The aim of this research is to investigation the optimization of the machining parameters (spindle speed, feed rate, depth of cut, diameter of cutter and number of flutes of cutter) of surface roughness for free-form surface of composite material (Aluminum 6061 reinforced boron carbide) by using HSS uncoated flat end mill cutters which are rare use of the free-form surface. Side milling (profile) is the method used in this study by CNC vertical milling machine. The purpose of using ANFIS to obtain the better prediction of surface roughness values and decreased of the error prediction value and get optimum machining parameters by using Taguchi method for the best surface roughness at spindle speed 4500 r.p.m, 920mm/rev feed rate, 0.6mm depth of cut, 10mm diameter, 2 flute.